The Growth of Oyster Mushroom on Ramie Chip Waste-Derived Media was Accelerated by Rice-washed Water - Budiono, Ruly; Washfanisa, Handina Alya; Mutaqin, Asep Zainal; Kusmoro, Joko; Nurzaman, Mohamad; Setiawati, Tia; Hasan, Rusdi (UIN Sunan Gunung Djati Bandung, 2024)
Rice-washed water is wastewater resulted from the rice cleaning process that is rich in nutrients. The use of ramie chip waste can be considered a potential substrate due to its lignocellulosic nature, similar to other wastes studied. This study aimed to examine the effect of rice-washed water on the mycelium and pinhead growth of white oyster mushrooms grown in the ramie chip waste as the growing medium. The experiment was conducted for three months using a completely randomized design with four rice-washed water treatments and six replications. The rice-washed water concentration treatments were 0% (K0), 25% (K1), 50% (K2), and 100% (K3), which were added to the ramie chip waste as the growing medium for white oyster mushroom. The time of mycelium propagation velocity, the time the first pinhead appearance, the number of mushroom bodies, and the largest cap diameter were observed. The results showed that ramie chip waste-derived media was suitable to cultivate white oyster mushrooms. Adding 100% rice-washed water to the media significantly affected the speed of mycelium propagation (16.51 days) compared to control (30 days) and the appearance of the first pinhead (31.5 days) compared to control (38.5 days) as well as the number of fruiting bodies of mushroom (8.8) compared to control (6.2). However, the rice-washed water application did not significantly affect the diameter of the largest mushroom cap.